Evaluation of compliance and adherence to medications in diabetic and/or hypertensive patients during the lockdown period and the effect of COVID-19 lockdown on blood glucose levels and blood pressure levels - Renuka BG; Kandagaddala Yaswath; Shweta R Chittawadgi; Yogeshwar; Sushma HK; Narendranath Sanji (Asian Journal of Medical Sciences, 2024)
Background: To contain the COVID-19 pandemic, a nationwide lockdown was imposed, which affected the lives of people with diabetes and hypertension as the patients were not able to regularly follow up with the doctor. Aims and Objectives: This prospective observational study was conducted to find out the compliance and adherence to oral hypoglycemic agents and antihypertensives during lockdown, to consult with doctors during lockdown, and also to analyze the effect of lockdown on blood glucose levels and blood pressure control by comparing the pre- and post-lockdown blood pressure and blood glucose levels. Materials and Methods: A prospective observational study was conducted on 100 participants aged between 35 and 85 years. They were studied by a questionnaire for a period of 3 months. The majority belonged to the 55–65 years of age group, and a male predominance was seen across all age groups. The changes in lifestyle habits of the participants during lockdown and complications due to diabetes and hypertension were also studied. Results: There was a statistically significant decrease in the adherence to prescribed medications during lockdown due to various reasons, the most important of which was the lack of access to personal consultation with the doctor during lockdown. Patients also could not follow their diet and physical exercises due to lockdown. All these factors led to poor control of blood pressure and blood glucose levels, as evidenced by comparing the pre- and post-lockdown blood glucose levels and blood pressure. Conclusion: This study concludes that there was a significant decrease in adherence to medications during the COVID-19 lockdown and there was poor control of blood pressure and blood glucose levels due to the lockdown period.